Civil Liability of Business Actors Selling Sunscreen on Tik-Tok Social Media Containing Fake Sun Protection Factor (SPF) - Naily Amalia; Dwi Aryanti Ramadhani (Journal of Law, Politic and Humanities, 2024)
This research discusses the business actors selling sunscreen with fake SPF content that endangers consumers.The purpose of this research is to find out the civil liability of business actors and to find out consumer efforts to obtain such liability.This research uses normative juridical legal research with a case approach and statutory approach.From this research it can be concluded that the actions of business actors are unlawful acts in accordance with article 1365 of the Civil Code and violate the consumer protection law so that they can be held liable in the form of compensation in accordance with applicable regulations.Consumer efforts to obtain their right to compensation can be done in a non-litigation manner.